Xúc tác Pt/WO3-ZrO2 trên vật liệu mao quản trung bình SBA-15 trong phản ứng isome hóa n-heptan - Thuận, Ngô Thị; Núi, Phạm Xuân (Vietnam Journal of Chemistry, 2014)
WO3/ZrO2(W/Z) mixed oxides supported on SBA-15 were prepared. Their acidities and catalytic activities in n-heptane isomerization were examined. For the mesoporous silica SBA-15 was pound to retain after loading with W/Z mixed oxide. HR-TEM photographs shown that tungstated zirconia was dispersed inside the mesoporous channels of SBA-15 and that the surface area and pore volume decreased with the loading. The mesoporous SBA-15 supports played an important role in stabilizing the mixed oxide W/Z with Pt 1%.wt catalyst.